Por uma sistemática didática: estudos semânticos voltados ao ensino de Língua Portuguesa no Ensino Médio - Souza, José Wellisten Abreu de (2017)
It may be observed the development of several grammatical studies intended for syntactic analysis of the language overtime. On the other hand, there are few studies intended for semantic analysis of linguistic phenomena. Therefore, we have as the general objective of this thesis: to analyze how the aspects related to signification are presented in Portuguese language textbooks used at High School level. In order to do so, we tried to a) identify the phenomena of semantic scope which are most approached in textbooks, b) analyze how the most recurrent phenomena are explored in the component materials of the corpus; c) discuss a proposal of didactic approach in Semantics for the curricular contents of Portuguese Language and, finally, d) to propose a basic list of contents for the syllabus which associate the importance of the semantic level with the teaching of Portuguese Language. The corpus of analysis of this research is composed of 27 activities present in the following textbooks: Português: linguagens (CEREJA; MAGALHÃES, 2010), Língua Portuguesa: linguagem e interação (FARACO; MOURA; MARUXO JÚNIOR, 2010); Português: gramática, literatura, produção de texto (SARMENTO; TUFANO, 2010) e Português: contexto, interlocução e sentido (ABAURRE, M.L.; ABAURRE, M.B.; PONTARA, 2008). We justify the importance of the adoption of the textbook corpus because we believe that in this supporting material it is possible to constitute a qualitative analysis which allows to present the contribution and importance of a didactic systematization of Semantic contents in relation to Portuguese Language Teaching. In the analysis of this research, we dealt with the following phenomena due to their greater recurrence: semantic-lexical – synonymy, antonyms and ambiguity –, as well as aspects related to the semantic-grammatical nature of the words in which the meaning effects of certain grammatical constructions such as conjunctions, adverbs, and prepositions. As for semantic-lexical aspects, this research is mainly based on Ilari and Geraldi (2006) and Lyons (1979; 1987; 1997). In terms of semantic-grammatical aspects, we were mainly theoretically supported by Travaglia (2002), Leite (1970; 1979) and Castilho (2010; 2014). Working with signification is fundamentally important for the establishment of the linguistic instrumentalization of the students, and this fact suggests the composition of a theoreticalmethodological proposal which we named as Didactic Semantics.